DETERMINAN PERILAKU TAX AVOIDANCE - Imelda Retno Putri Widia Ningrum; Evi Maria (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2021)
Abstract This study aims to see and analyze the effect of profitability, leverage, Corporate Social Responsibility (CSR), company size (SIZE) on tax avoidance. This research was conducted on the Indonesia Stock Exchange (BEI). The population used for this research is 54 companies in the consumer goods industry sector. Sampling researchers used non-probability sampling-purposive sampling method obtained by 21 companies with observation time of 2016-2019 in order to obtain 84 samples. The method of analysis with path analysis uses IBM's SPSS 25 program. This study empirically examines the effect of profitability, leverage, Corporate Social Responsibility (CSR), and company size on tax avoidance in manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. The research results prove that (1) profitability has no significant effect on tax avoidance, (2) Leverage has no effect on tax avoidance, (3) Corporate Social Responsibility has no effect on tax avoidance, (4) Firm size has no effect on tax avoidance.